Kompetencja międzykulturowa a umiejętność sporządzenia dokumentów aplikacyjnych (na materiale języka niemieckiego) - Bawej, Izabela (Neofilolog, 2023)
On the job market today, people with a (very) good knowledge of a foreign language, such as German, are in demand. Candidates are required to submit their application documents in this language. Unfortunately, having grammatical correctness and a rich vocabulary are not enough to write a job application and a CV. In order to prepare these documents correctly, it is necessary to know the differences between one’s own and the other culture, in this case the culture of German-speaking countries. The aim of this paper is to present the findings of an exploratory study examining errors students made naming and expressing selected elements of the non-lingual reality that represent a specific kind of reflection of new and often foreign realities in covering letters and CVs. Due to the limited framework of this paper, it is focused on intercultural aspects. While these seem to be very simple, they may cause difficulties because of the characteristic way they are presented in the acquired language, such as the use of courtesy rules, the recording of the date, giving of personal data, writing about foreign languages skills or providing information about a driving licence.